Cardinal spline wavelet decomposition based on quasi-interpolation and local projection - Ahiati, Veroncia Sitsofe (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Mathematics))--University of Stellenbosch, 2009.